STIR-RST: A Software tool for reactive smart tracer studies. (January 2021) - Bottacin-Busolin, A.; Dallan, E.; Marion, A.
Abstract: The introduction of "smart" tracer techniques in recent years has provided new ways to investigate sediment-water interactions and microbial activity in stream corridors. In this study, the formulation of the STIR model (Marion et al., 2008) is extended to represent the transport and transformation of Resazurin-Resorufin smart tracers, and an object-oriented toolbox, STIR-RST, is presented for model evaluation and calibration. STIR-RST allows different storage processes to be represented by specific residence time distributions (RTDs), with two possible arrangements of the storage zones: nested (in-series) or competing (in-parallel). The application of STIR-RST to field tracer data is demonstrated assuming two storage zones with exponential RTD. Results show that the assumption of two storage zones provides a better approximation of the observed BTCs compared to that of a single storage zone, at the cost of higher parameter uncertainty. Similar fits are obtained for nested and competing zone arrangements. Highlights: A general residence time distribution model is presented for smart tracer studies. STIR-RST allows simulation of tracer breakthrough curves and model calibration. The application of the software is demonstrated with Resazurin-Resorufin field data. Good data fits are obtained assuming two storage zones with exponential RTD. Similar fits are obtained for nested and competing arrangements of the storage zones.